Making Sense of God: How I Got to the Brain - Ashbrook, James B. (Zygon, 1996)
Abstract. I describe the development of my work in relating brain research and religion from my personal roots in my family of origin through my professional responsibilities as a pastor, a clinician, and a theological educator to my developing what I call “a neurotheological approach” to faith and ministry. My early correlations gave simplistic attention to bimodal consciousness as an interpretive tool for understanding religion. Subsequently came a more sophisticated exploration of whole-brain functioning and suggested cultural correlates. Currently, I am explicating tae humanizing brain as reflective of our living in an open system, a universe that is unfolding and evolving, a universe in the hands of the whole-making, integrating, emerging God whose reality far exceeds the insights of cultural construction. As we humans relate to this God, attachment and aspiration are reciprocal.